Opinion of Reproductive Mothers on Gender Issues: A Cross Sectional Study in Sub-Urban West Bengal - Basu, Gandhari; Biswas, Subikas; Roy, Suman Kumar (National Journal of Community Medicine, 2017)
Background: Literatures reported gender preference among women in different parts of India. The study was conducted to know the opinion of mothers on different areas of gender inequalities, presence of gender preference and the associated factors. Methodology: The present cross sectional, descriptive study was done among mothers residing in a sub urban community of Nadia district. Data was collected by direct interview. Results: Among the ninety nine (99) participating mothers, most were Hindu (96), homemaker (91), lived in nuclear family (76) with mean age of 30.89 years. One out of every five mother was illiterate. 23.2% mothers had abortion and 63.6% practiced contraception. Eighty six mothers opined that a couple should have one or two children. Difference in opinion favouring male child was noted. There was no difference in seeking health care, providing more education, sharing of food for either sex. Preference for boy child was similar as girl child (31.3% vs. 26.3%). Conclusions: In spite of presence of inequalities in opinion, there was no significant gender preference present for either sex. Acculturation and improved female literacy could make the scenario more glorified.